2022
DOI: 10.3390/polym14245548
|View full text |Cite
|
Sign up to set email alerts
|

Melt Temperature Estimation by Machine Learning Model Based on Energy Flow in Injection Molding

Abstract: Highly reliable and accurate melt temperature measurements in the barrel are necessary for stable injection molding. Conventional sheath-type thermocouples are insufficiently responsive for measuring melt temperatures during molding. Herein, machine learning models were built to predict the melt temperature after plasticizing. To supply reliably labeled melt temperatures to the models, an optimized temperature sensor was developed. Based on measured high-quality temperature data, three machine learning models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Additionally, the SHapley Additive exPlanations (SHAP) technique was applied to Reaction Chemistry & Engineering Paper explicate the output of machine learning models, providing insights into the importance of individual input features in predicting a specific model outcome. [33][34][35]…”
Section: Modelling With Machine Learning Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the SHapley Additive exPlanations (SHAP) technique was applied to Reaction Chemistry & Engineering Paper explicate the output of machine learning models, providing insights into the importance of individual input features in predicting a specific model outcome. [33][34][35]…”
Section: Modelling With Machine Learning Techniquesmentioning
confidence: 99%
“…SHAP values provide a more localized interpretation by pinpointing the average contribution of each feature, calculated by considering all possible combinations of feature permutations. 35 The SHAP values for Run1 and Run2 in the XGB model predicting FS are visualized in Fig. 6.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…Polymerization is the process through which monomers undergo chemical bonding to form polymer chains. Polymers possess a wide range of properties, including mechanical strength, flexibility, high temperature resistance, and electrical conductivity, which are identified by their distinctive composition and molecular structure [ 6 , 7 , 8 , 9 ]. They are extensively employed in several productions such as packaging, automotives, manufacturing, textiles, electronics, medical, and others due to their diverse features.…”
Section: Introductionmentioning
confidence: 99%
“…Shams-Nateri’s study also demonstrated an application of Neural Networks to relate the color of fibers in the mentioned directions [ 12 ]. Jeon constructed machine learning models to predict the melting temperature after plasticization [ 13 ]. Joo devised three models to predict the physical properties of PP composites, employing three distinct machine learning (ML) methods: Multiple Linear Regression (MLR), Deep Neural Network (DNN), and Random Forest (RF) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%